Pembangunan Sistem Pengelolaan Administrasi Ujian TOEFL berbasis Website - Muhammad Ifan Farisqi; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One way to deepen understanding of the use of English is to take the TOEFL test. The initial stage before taking the TOEFL exam is administering the exam. The administrative management stage of the registrant must complete the various data provided, such as carrying out registration activities and financial recapitulation. With the current conditions, where the Covid-19 pandemic makes activities carried out offline become completely online. The pandemic caused problems because the relevant agencies limited physical interaction in terms of administering the TOEFL exam. The interaction above is an interaction between the manager and prospective registrants in conducting administration. Administrative activities include registration, value announcement reporting processes, distribution of certificates and financial management processes including financial entry and exit records, financial information and financial reports. Based on the problems above, the authors provide an idea to create a Website-Based TOEFL Test Administration Management System to facilitate a more effective TOEFL service, namely reducing time and energy for participants when carrying out administrative and worker activities in terms of administering TOEFL exam administration and time efficiency. The system implemented can accommodate announcements of exam openings, verification of exam registration via email, automatic payments using midtrans, score announcements and financial management. In implementing the system to be built using the Laravel framework tool. System testing is done by unit testing, integration, validation, and compatibility.